2020
DOI: 10.1101/2020.07.16.206722
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single cell characterization of a synthetic bacterial clock with a hybrid feedback loop containing dCas9-sgRNA

Abstract: Genetic networks that generate oscillations in gene expression activity are found in a wide range of organisms throughout all kingdoms of life. Oscillatory dynamics facilitates the temporal orchestration of metabolic and growth processes inside cells and organisms, as well as the synchronization of such processes with periodically occurring changes in the environment. Synthetic oscillator gene circuits such as the ‘repressilator’ can perform similar functions in bacteria. Until recently, such circuits were mai… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 49 publications
(52 reference statements)
0
11
0
Order By: Relevance
“…CRISPRi has been rapidly adopted because it can exert regulatory control without having to mutate the target; however, it only imparts a single on/off signal. To this end, depression/derepression can be used to inactivate the effects of CRISPRi in the control of native genes (Nielsen & Voigt, 2014; Weinberg et al , 2017; Moser et al , 2018; Henningsen et al , 2020). For example, CRISPRi/a has been used to dynamically repress or activate enzymes to control carbon flux in metabolic engineering applications (Moser et al , 2018; Peng et al , 2018; Lu et al , 2019; Tian et al , 2019; Fontana et al , 2020b).…”
Section: Discussionmentioning
confidence: 99%
“…CRISPRi has been rapidly adopted because it can exert regulatory control without having to mutate the target; however, it only imparts a single on/off signal. To this end, depression/derepression can be used to inactivate the effects of CRISPRi in the control of native genes (Nielsen & Voigt, 2014; Weinberg et al , 2017; Moser et al , 2018; Henningsen et al , 2020). For example, CRISPRi/a has been used to dynamically repress or activate enzymes to control carbon flux in metabolic engineering applications (Moser et al , 2018; Peng et al , 2018; Lu et al , 2019; Tian et al , 2019; Fontana et al , 2020b).…”
Section: Discussionmentioning
confidence: 99%
“…In this setup, the dCas12a-based circuit displayed more regular oscillations than the one relying on dCas9 [128]. Additionally, a new preprint explored a hybrid oscillator in which one of the three initial TFs of the repressilator is replaced by a dCas9-gRNA complex [129]. In this study, decoy binding sites for the dCas9-gRNA complex have been suggested to play a role in generating the required non-linearity in the absence of cooperativity.…”
Section: Crispr-based Synthetic Circuitsmentioning
confidence: 93%
“…Indeed, a lack of non-linearity poses major challenges for building important synthetic networks such as oscillating or multistable circuits, which require non-linear gene expression control to operate [124][125][126][127]. However, recent results demonstrate that it is actually possible to build CRISPR-based multistable and dynamic circuits such as a toggle switch and an oscillator (see 'CRISPR-based synthetic circuits' section for details) [69,128,129].…”
Section: Possibilities and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite successes in creating dCas-based endpoint 3,13,14 and dynamic [15][16][17] circuits, challenges remain when circuits are scaled up from just a few CRISPRi ele-ments. 18 In fact, CRISPR's reprogrammability is also the source of its greatest weaknesses: because a shared pool of dCas proteins is drawn on simultaneously from all active elements, or nodes, in a circuit, it is possible for downstream nodes to interfere with the regulatory activity of those further upstream, an effect called retroactivity.…”
Section: Introductionmentioning
confidence: 99%